Incorporating Financial Statement Information to Improve Forecasts of Corporate Taxable Income - Green, Danielle H.; Henry, Erin; Parsons, Sarah M.; Plesko, George A. (The Accounting Review, 2022)
ABSTRACT We examine whether public financial statement information is incrementally useful in forecasting confidential taxable income. More precise firm-level taxable income forecasts can improve policymakers' modeling of the tax system and the analysis of proposed changes in corporate tax law, while more accurate macro-level forecasts of corporate taxable income can improve estimates of corporate tax revenues, a significant component of the federal budget. We find the addition of financial statement information improves firm- and industry-level estimates of future taxable income by primarily providing more timely information, but also through accruals. Our results suggest that macroeconomic forecasts of taxable income may be further improved by the aggregation of firm-level forecasts that are generated using financial statement information. Importantly, our results are driven primarily by tax information in financial statements. We also contribute to the research on the information content of financial statement information for forecasting economic activity. JEL Classifications: M41; M48; H25.